Market underreaction to open market share repurchases on the JSE - N. Wesson; C. Muller; M. Ward (South African Journal of Business Management, 2014)
This study examined the long-term performance of open market share repurchase announcements made by companies listed on the JSE during their reporting periods including 1 July 1999 to 2009. A total of 195 open market share repurchase announcements were identified. A maximum outperformance of about 35% was found on day t+550 (about two years subsequent to the announcement). After splitting the sample into 'value' (low P/E ratio) and 'growth' shares (high P/E ratio), it was found that the outperformance was almost entirely confined to the value portfolio, reaching a maximum of about 80% by day t+630 (about two-and-a-halfyears subsequent to the announcement). This study applied a more robust research methodology than used in earlier South African research on this topic; it also used an improveddataset and extended the research period, compared to other research. The results of this study showed much higher positive abnormal returns than were found in earlier international and South African studies. Investors should takeadvantage of the informational value of open market repurchase announcements and the related significant abnormal returns to be earned.
Keywords: 650